(untitled) (Eastern Journal of Medical Sciences, 2018)
Objectives: We aimed to develop a subjective family happiness scale and analyzed its ?validation ?and reliability. Methods: To develop, a scale for measuring subjective family happiness, an item pool ?was ?created. A 19-item scale was formed using Delphi rounds and seeking expert opinions. ?The ?instrument was applied to 300 participants >18 years of age. Six items were excluded ?according ?to participant opinions (n=2) or due to low factor loads (n=4). Results: Kaiser-Meyer-Olkin coefficient was found as 0.93, and the Cronbach Alpha ?internal ?reliability coefficient was calculated as 0.93. Exploratory factor analysis confirmed ?that the scale ?had a two-dimension structure and these dimensions were named as ??‘happiness’ and ??‘unhappiness’. ?Conclusion: The scale was valid and reliable for the measurement of subjective family ?happiness ?in family members of >18 years. This instrument can be utilized by family ?physicians, family ?counsellors, family therapists, psychiatrists, and psychologists in making ?decisions about the ?problems related to the families?.?